Edukasi Pembuatan Detergen Cair sebagai Upaya Pemberdayaan Ibu-Ibu PKK di Perumahan Graha Rawa Bangun Kelurahan Tuah Karya Kecamatan Tuah Madani Kota Pekanbaru - Nurfatihayati; Al’farisi, Cory Dian; Mutamima, Anisa; Utama, Panca Setia; Fadli, Ahmad; Azis, Yelmida; Sunarno; Suhendri; Habib, Alltop Amri Ya; Alel, Ariya Eka; Hastuti, Ririn Puji; Yolanda, Yogi; Syawal, Ferdy Ashari (PELITA NUSA TENGGARA, 2026)
This community service activity aimed to enhance the knowledge and skills of PKK women in producing liquid detergent as an effort to promote community empowerment and household self-reliance. The activity was conducted in Graha Rawa Bangun Housing Area, Tuah Karya Village, Tuah Madani District, Pekanbaru City. The implementation methods included educational sessions, hands-on training on liquid detergent production, and evaluation using pre-test and post-test questionnaires. The training materials covered the introduction of raw materials, the function of each component, production procedures, and safety aspects related to the use of household chemicals. The evaluation results indicated a significant improvement in participants’ knowledge. The average level of participants’ knowledge increased from 16% in the pre-test to 85% in the post-test, with an overall improvement of 69%. Improvements were observed in both the understanding of primary cleaning agents and auxiliary ingredients in liquid detergent formulations. These findings demonstrate that an educational approach integrating simple scientific explanations with practical training is effective in enhancing participants’ capacity. The outputs of this activity include improved knowledge and skills of PKK women in producing safe and applicable liquid detergent, which has the potential to support household independence and community empowerment.